Analisis Efektivitas Metode Deep Soil Mixing dalam Meningkatkan Stabilitas Tanah Lunak pada Konstruksi Jalan Tol - Ababiel Ashabussidiq; Jerrico Naufal Hibban; Rifqi Brilyant Arief; Rinda Karlinasari (Journal of Engineering and Applied Technology, 2026)
The construction of toll roads on soft soil frequently encounters geotechnical problems in the form of excessive ground settlement and low embankment stability, which may lead to structural failure if appropriate ground improvement measures are not implemented. Deep Soil Mixing (DSM) is a ground improvement technique in which in-situ soil is mixed with a binding agent to increase shear strength and reduce soil compressibility. This study aims to analyze the effectiveness of the DSM method in improving the stability of soft soil for toll road construction and to evaluate the influence of variations in column spacing and depth on soil deformation and safety factors. The study was conducted as a case study of the Probolinggo–Banyuwangi Toll Road Development Project, Package 2, at STA 16+550–STA 16+600, using analytical approaches and numerical modeling based on the finite element method with PLAXIS 2D software. Analyses were performed for conditions without ground improvement and with DSM improvement using two configurations, namely a column spacing of 1.5 m with a depth of 8 m and a column spacing of 1 m with a depth of 6 m. The results indicate that the application of the DSM method significantly increases the safety factor and reduces soft soil deformation, with a closer column spacing configuration demonstrating more optimal performance in enhancing embankment stability.